A primary tumor of mixed histological type is a novel poor prognostic factor for patients undergoing resection of liver metastasis from gastric cancer. (10th April 2017) - Ikari, Naoki; Taniguchi, Kiyoaki; Serizawa, Akiko; Yamada, Takuji; Yamamoto, Masakazu; Furukawa, Toru
Abstract: Background: Surgical resection can be an option for the treatment of metastatic liver tumors originating from gastric cancer; however, its prognostic impact is controversial. The aim of this study was to identify prognostic factors in patients with surgical resection of liver metastasis from gastric cancer. Methods: We retrospectively analyzed the clinicopathological features of 38 consecutive patients undergoing hepatectomy for metastatic tumors from gastric cancer in our institution between 1990 and 2014. Results: The median overall survival of the patients was 28 months. The 5‐year survival rate was 33.9%. Primary tumors of a mixed histological type, and residual tumors during the course of treatment were identified as significant independent poor prognostic factors. Conclusions: Histological evaluation of primary tumors may aid to identify patients suitable for undergoing surgical resection of liver metastasis from gastric cancer. Abstract : Highlight To identify suitable patients for surgical resection of liver metastasis from gastric cancer, Ikari and colleagues retrospectively analyzed 38 consecutive patients undergoing hepatectomy for gastric cancer metastasis. They found that primary tumors of mixed histological type and residual tumors during the course of treatment were significant independent poor prognostic factors.